THE EFFECT OF WORK STRESS, WORK LOAD, AND WORK ENVIRONMENT ON TURNOVER INTENTION AT PT IMA MOUNTAZ PROSPERITY IN LHOKSEUMAWE - Mia Claudia; Marbawi; A Hadi Arifin; Khairawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to determine and analyze the influence of Work Stress, Workload, and Work Environment on the turnover intention of employees of PT. Ima Montaz Sejahtera Lhokseumawe. At PT Ima Montaz Sejahtera, a company that produces bottled drinking water, the turnover intention rate showed an increase from 2020 to 2022. Based on the data obtained, the turnover rate in 2020 was 1.9%, in 2021 it increased to 7.8%, and in 2022 it reached 12%. Many employees feel burdened by the workload and lack of support from management, which causes them to want to leave the company. The sampling method in this study uses simple random. The sample size is calculated using the Slovin formula. In this study, the sample size was set at 55 respondents of PT Ima Montaz Sejahtera Lhokseumawe employees. The sampling technique is done by simple random sampling, which is a simple random sampling technique where each respondent or member of the population has the same opportunity to be selected as a sample. It was concluded that every year there is an increase in the number of employees who leave the company which has increased every year. Based on the results of research that has been conducted regarding the effect of workload, work stress and work environment on turnover intention on employees of PT. Ima Mountaz Sejahtera Lhokseumawe, the following conclusions can be drawn. Workload has a significant positive effect on increasing turnover intention of employees of PT Ima Mountaz. Work stress has a significant positive effect on increasing turnover intention of employees of PT Ima Mountaz. The work environment has a significant positive effect on increasing turnover intention of employees of PT Ima Mountaz.